2010
DOI: 10.1380/ejssnt.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Electron Transport and Scattering in Bi(111) Surface States

Abstract: The Bi(111) surface exhibits a pronounced surface state which acts as dominant transport channel for electric current. We performed in situ four-point probe resistance measurements for thin Bi(111) films on Si(001) to study electron scattering effects in this two-dimensional (2D) electron gas. The surface morphology was manipulated by additional deposition of Bi at 80 K. A linear increase of surface resistance was measured at extremely low coverage of less than 1 % of a bilayer (BL) and the slope gradually dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The film quality was verified in-situ by low-energy electron diffraction (LEED) and STM. The low-temperature electron transport in such Bi films is dominated by a high density of surface-state electrons of about 10 13 /cm 2 and a negligible carrier concentration in the film bulk [28,29]. Submonolayer (ML) amounts of single-atom metal impurities were deposited onto the bare Bi films at 5 K into the STM without detaching the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The film quality was verified in-situ by low-energy electron diffraction (LEED) and STM. The low-temperature electron transport in such Bi films is dominated by a high density of surface-state electrons of about 10 13 /cm 2 and a negligible carrier concentration in the film bulk [28,29]. Submonolayer (ML) amounts of single-atom metal impurities were deposited onto the bare Bi films at 5 K into the STM without detaching the sample.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 For the homoepitaxial Bi(111) system, it has been shown that the change of conductance upon adsorption can be indeed be accurately modeled. 9,27 Here, we will extend this model including charge transfer (CT) and atomic steps of the Bi(111) films, which serve as perfect sinks for the diffusing monomers. The set of rate equations that reveal the main features of the G/G 0 curve (shown in Fig.…”
Section: E Nucleation Of Tb Atoms: Simulationmentioning
confidence: 99%
“…The sheet carrier density in this surface state, as deduced from the Fermi surface map or Hall measurements, is of the order of n ss ∼ 0.5 − 1.5×10 13 cm −2 , which for film thicknesses below 10 nm is almost two orders of magnitude higher than the projected carrier density in the bulk (∼ 10 11 cm −2 ) [4,8,9]. In recent works it has been confirmed that bulk conduction is negligible in ultrathin Bi films at low temperatures [9,10].…”
mentioning
confidence: 92%